COMPARISON BETWEEN COMPUTED TOMOGRAPHIC CHARACTERISTICS OF THE MIDDLE EAR IN NONBRACHYCEPHALIC AND BRACHYCEPHALIC DOGS WITH OBSTRUCTIVE AIRWAY SYNDROME. Issue 2 (14th January 2016) - Salgüero, Raquel; Herrtage, Michael; Holmes, Mark; Mannion, Paddy; Ladlow, Jane
Abstract : Prevalence of subclinical middle ear lesions in dogs that undergo computed tomography (CT) and magnetic resonance imaging of the head has been reported up to 41%. A predisposition in brachycephalics has been suggested, however evidence‐based studies are lacking. Aims of this retrospective cross‐sectional study were to compare CT characteristics of the middle ear in groups of nonbrachycephalic and brachycephalic dogs that underwent CT of the head for conditions unrelated to ear disease, and test associations between thickness of the soft palate and presence of subclinical middle ear lesions. One observer recorded CT findings for each dog without knowledge of group status. A total of 65 dogs met inclusion criteria (25 brachycephalic, 40 nonbrachycephalic). Brachycephalic dogs had a significantly thicker bulla wall ( P = 2.38 × 10 −26 ) and smaller luminal volume ( P = 5.74 × 10 −20 ), when compared to nonbrachycephalic dogs. Soft palate thickness was significantly greater in the brachycephalic group ( P = 2.76 × 10 −9 ). Nine of 25 brachycephalic dogs had material in the lumen of the tympanic cavity, compared to zero of 45 of nonbrachycephalics. Within the brachycephalic group, a significant difference in mean soft palate thickness was identified for dogs with material in the middle ear (12.2 mm) vs. air‐filled bullae (9 mm; P = 0.016). Findings from the current study supported previous theories that brachycephalic dogs have a greater prevalence of subclinical middle ear effusion and smaller bulla luminal size than nonbrachycephalic dogs. Authors recommend that the bulla lumen volume formula previously developed for mesaticephalic dogs, (−0.612 + 0.757 [lnBW]) be adjusted to 1/3(−0.612 + 0.757 [lnBW]) for brachycephalic breeds.